Rs.60,000 Crores:Will the Magic Number Solve the Plight of the Indian Farmers? - Ganapathi, R.; Sannasi, S. (Indian Journal of Marketing, 2009)
Since independence, the governments-the Central and the State-have been taking constant efforts to develop the agricultural sector. In every Five year plan, considerable amount is being allotted to the farm sector, with ample budgetary supports. The development of agriculture in India since independence is remarkable. Advanced technology is introduced in farming sector. Hybrid seeds for majority of the crops were invented. NABARD provides high incentives such as financial assistance to the farmers in the form of crop loans, long term loans for erection of Pump sets and digging wells, etc. Still the plight of the Indian farmer today is unenviable. Majority of them are still under the chetches of private moneylenders. The farmers are not able to repay the loan to the banks and local money lenders. Many of them migrate to industrial towns and settle there facing many difficulties in their daily life. It is miserable to see that farmers in Andhra Pradesh and Maharashtra states commit suicide along with their family members. Though the government takes initiatives and various measures in every budget, we could not stop the suicide attempt by the farmers in many places. Keeping the above in mind, the article on "Rs.60,000 CRORES: WILL THE MAGIC NUMBER SOLVE THE PLIGHT OF THE INDIAN FARMERS?" is written, to examine the possible impact of the budget on the agriculturists.